Pengaruh Tekanan Pembriketan dan Persentase Briket Campuran Gambut dan Arang Pelepah Daun Kelapa Sawit terhadap Karakteristik Pembakaran Briket - Nugraha, Andy; Widodo, Agung Sugeng; Wahyudi, Slamet (Rekayasa Mesin, 2017)
Briquettes mixture of peat and charcoal leaf midrib palm oil is one of the alternative energy for replacing fossil fuel energy. It is environmentally friendly and abundant in Indonesia, mainly in South Kalimantan. In this study, the percentage of briquettes mixture of peat and charcoal leaf midrib of palm oil were 50%:50%, 60%:40%, 70%:30%, 80%:20% and 90%:10%, respectively. In addition, 1 gram of starch was added as an adhesive for every variation of briquettes mixture. In briquetting process, the pressures were 10 kg/cm2, 20 kg/cm2 and 30 kg/cm2. The combustion characteristics ofÂ  briquettes was tested, then it was compared by subbituminous coal briquettes. The results show, ignition delay of briquettes decrease by increasing additional percentage of peat, however extend the burning time of briquettes, consequently the burning rate decrease and the briquettes temperature becomes low. Briquetting pressure affects the combustion characteristics of briquettes. Ignition delay of briquettes decrease by the pressure. On the other hand, extend the burning time of briquettes and decrease the burning rate, however combustion temperatures of briquettes increases. The results also show a comparison of mixture briquettes peat and charcoal palm leaf midrib with subbituminus coal briquettes. The subbituminous coal briquettes produces higher combustion temperature, the longer combustion process and the lowestÂ  combustion rate.Â